Mapping the distribution of radial artery atherosclerosis by optical coherence tomography - Yuntao Wang; Rui Yan; Zixuan Li; Zijing Liu; Yujie Wang; Jiahui Song; Senhu Wang; Yongxia Wu; Haotian Wang; Jincheng Guo (BMC Medical Imaging)
Abstract Background Radial artery plaque (RAP) can influence the function of arterial conduits after revascularization and hinder the maturation of arteriovenous fistulas in patients undergoing hemodialysis patients. However, the preferred in vivo sites for RAP development have not been systematically investigated. This study measured and evaluated RAP to map the distribution of RAP in the radial artery (RA) using optical coherence tomography (OCT). Methods OCT images of the entire RA in 300 patients at 1 mm intervals were analyzed to assess RAP phenotypes and measure the distance of RAP from the radial artery ostium. The RA was evenly divided into three segments: proximal, middle, and distal. Patients were categorized into two groups: the RAP group (n = 68) and the non-RAP group (n = 232). Results Among the 300 patients with 300 radial arteries studied, 68 patients (22.7%) developed 180 distinct RAPs. The distal segment was the most susceptible to RAP formation (51 patients; 17.0%).In plaque level analysis, Most RAPs (55%) were located ≥ 150 mm from the RA ostium. The distal segment exhibited a significantly higher median cumulative plaque index compared with the proximal and middle segments (p = 0.031). Logistic regression analysis identified aging, smoking, diabetes mellitus, and multi-vessel coronary disease (MVCD) as independent risk factors for RAP occurrence. Conclusions RAP was observed in 22.7% of patients with acute coronary syndrome (ACS), with a predominant localization in the distal segment, both at the patient and plaque level. Significant risk factors included aging, smoking, diabetes mellitus, and MVCD.